2019
DOI: 10.1016/j.indcrop.2018.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress adaptation modulates plant secondary metabolite production in Salvia dolomitica Codd

Abstract: Sages are important medicinal and aromatic plants. While Salvia officinalis and S. miltiorrhiza have been widely studied, poor information are available on S. dolomitica which is recently addressing attention for its antiplasmodial and anti-inflammatory properties. The current study investigated the performances and the metabolic profile of this minor species in response to drought stress. Plants were exposed to three treatments: control, moderate drought stress, or severe drought stress.Changes in growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 66 publications
5
45
0
Order By: Relevance
“…[184] Authors recommend the cultivation of S. lavandulifolia, T. capitatus and T. mastichina, because there are no differences in essential content, but if there is a water-saving rate of 30 %, while the essential oil content decreased in L. latifolia and S. sclarea plants under water deficit conditions. EO content and quality of L. angustifolia and S. fruticosa seemed to increase under water stress conditions in a study of Chrysargyris et al [185] This behavior is confirmed also for S. dolomitica, [186] S. officinalis, [187] S. sinaloensis [188] and some Greek Oregano populations. [189] Foliar application of salicylic acid under water stress conditions increase EO content on T. kotschyanus.…”
Section: S Algeriensismentioning
confidence: 69%
See 1 more Smart Citation
“…[184] Authors recommend the cultivation of S. lavandulifolia, T. capitatus and T. mastichina, because there are no differences in essential content, but if there is a water-saving rate of 30 %, while the essential oil content decreased in L. latifolia and S. sclarea plants under water deficit conditions. EO content and quality of L. angustifolia and S. fruticosa seemed to increase under water stress conditions in a study of Chrysargyris et al [185] This behavior is confirmed also for S. dolomitica, [186] S. officinalis, [187] S. sinaloensis [188] and some Greek Oregano populations. [189] Foliar application of salicylic acid under water stress conditions increase EO content on T. kotschyanus.…”
Section: S Algeriensismentioning
confidence: 69%
“…EO content and quality of L. angustifolia and S. fruticosa seemed to increase under water stress conditions in a study of Chrysargyris et al . This behavior is confirmed also for S. dolomitica , S. officinalis , S. sinaloensis and some Greek Oregano populations . Foliar application of salicylic acid under water stress conditions increase EO content on T. kotschyanus .…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 91%
“…In a very different study, a similar phenomenon was demonstrated. Drought increased the level of ABA in Salvia dolomitica and increased the production of sesquiterpenes and the expression of FDP synthase that produces the substrate for sesquiterpene biosynthesis (Caser et al ., ). In a study on the influence of salt on volatile emission from tomato leaves, however, the results are less clear (Zhang et al ., ).…”
Section: Regulation Of Voc Biosynthesismentioning
confidence: 97%
“…The phytochemical characterisation of each sample was performed as previously described by Caser et al [48,49]. Briefly, the total anthocyanin content (TAC) was determined using the pH-differential method.…”
Section: Phytochemical Characterisationmentioning
confidence: 99%